2017
DOI: 10.1103/physrevb.96.075113
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical dissipation at a tip-induced Kondo onset

Abstract: The onset or demise of Kondo effect in a magnetic impurity on a metal surface can be triggered, as sometimes observed, by the simple mechanical nudging of a tip. Such a mechanically-driven quantum phase transition must reflect in a corresponding mechanical dissipation peak; yet, this kind of signature has not been focused upon so far. Aiming at the simplest theoretical modelling, we treat the impurity as an Anderson impurity model, the tip action as a hybridization switching, and solve the problem by numerical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…In this limit τ → ∞, we also have at our disposal the results of Ref. 1 , where we computed E diss for a SIAM with NRG, which gives numerically exact results. In that situation, the dissipation contained a large term proportional to Γ, plus a smaller Kondo contribution proportional to T K , albeit with logarithmic corrections not expressable as log T K , since the Kondo resonance is not simply a Lorentzian.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this limit τ → ∞, we also have at our disposal the results of Ref. 1 , where we computed E diss for a SIAM with NRG, which gives numerically exact results. In that situation, the dissipation contained a large term proportional to Γ, plus a smaller Kondo contribution proportional to T K , albeit with logarithmic corrections not expressable as log T K , since the Kondo resonance is not simply a Lorentzian.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work 1 we treated the same problem in the limit of vanishing frequencies, which is relevant when the Kondo effect can be switched on and off mechanically, as in an AFM experiment. Under the hypothesis of thermalization, we found that the dissipated energy is:…”
Section: A Zero Frequency Reviewmentioning
confidence: 99%
See 3 more Smart Citations